Decision Support System Penilaian Afektif Siswa Berdasarkan Standar Kurikulum Tingkat Satuan Pendidikan Menggunakan Metode AHP Studi Kasus SMA Muhammadiyah Parung - Ananda Novprico Syahdaya; Sewaka (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
SMA Muhammadiyah Parung in assessing student learning is determined not to be objective which creates problems among students and other parents and triggers social jealousy. That is determined by the proximity of the teacher to the parents of students. To avoid existing problems, one of the evaluations that must be assessed is the Affective Realm because the affective component greatly determines the success of student learning. The Decision Support System here helps make assessments in the affective domain and facilitates decision making in this case knowing problems related to attitude tendencies, interests, talents, social control and student learning readiness.